PSVIII-42 Effect of presynchronization using prostaglandin F2α prior to a shortened progesterone exposure in fixed-timed AI of crossbred beef cows nursing calves. (5th December 2019) - Rook, Whitney L; Powell, Jeremy; Cauble, Reagan; Rorie, Rick
Abstract: Presynchronization has been shown to improve AI pregnancy rates in dairy cattle, by improving the effectiveness of the initial GnRH treatment required for follicular control in estrous synchronization protocols. An experiment was designed to evaluate the effect of prostaglandin presynchronization in a fixed-timed AI (FTAI) protocol with a shortened progesterone exposure in beef cows. A total of 135 fall calving (September-November) crossbred beef cows from two locations were randomized to receive either: A) prostaglandin (25mg; Lutalyse, Zoetis, Kalamazoo, MI) administered two days prior to synchronization with GnRH (100mg; Factrel, Zoetis) and progesterone (1.38g P4 ; CIDR, Zoetis) for 6 days, or B) Control, the same synchronization protocol without Lutalyse pretreatment. On day 6 (Day 0: CIDR insertion) CIDR was removed and 25mg of prostaglandin was administered and 72 hours later fixed-timed AI with concurrent injection of 100mg of GnRH. Conventional frozen semen from Simmental-Angus sires was used for AI and fertile Angus bulls were used for pasture exposure. Pregnancy was determined by ultrasound 30 days after AI and again 30 days after clean-up bull exposure for 30 days. Statistical analysis was performed using the frequency procedure of SAS (Cary, NC) and significance was set at X 2 < 0.05. Pregnancy rate to timed AI was 71.4% for Treatment A compared to 80.3% for Treatment B (Control). Although these results were greater than previously reported at these research stations, there was no statistical difference (X 2 =0.23) between treatments. Overall pregnancy rates tended to be different (X 2 =0.06) and were potentially influenced by treatment or shortened exposure to progesterone in synchronization. Research supported by University of Arkansas Division of Agriculture.